A transformação do ordenamento jurídico brasileiro após o Caso Maria da Penha - Daré, Geisa Oliveira (Language and Law / Linguagem e Direito, 2022)
The a priori perception of the end of impunity for the aggressor clearly helps to prevent violence. Herein lies the importance of the social transformation of law. This article analyzes the main transformations of the Brazilian legal system in an attempt to combat domestic and family violence against women, as a consequence of the condemnation that Brazil suffered on April 4, 2001, by the Inter-American Commission on Human Rights, in the Case of Maria da Penha. It will be demonstrated that the former situation of neglect and disrespect for women’s rights in Brazil has been gradually rectified over the years since, having now reached an adequate level of legislative protection.